Alignment of Science and Technology With Islamic Principles Using Quantum Theory - Alwiyah Alwiyah; Syarief Nur Husin; Padeli Padeli; Mey Anggaraeni; Sulistiawati Sulistiawati (International Institute for Advanced Science & Technology (IIAST), 2021)
The wave-particle duality stranges and it is in dire need. This theory is put forward method based on the Koran and complemented by rational philosophical arguments. Explaining relevant Quranic verses, as well as the one-to-one relationship between the concept of pairing and the interviewee's principle, will help explain of the electron in detail. Shows that electrons all of which reflect the behavior of the wave-particle duality observed in experiments. Although physicists consider a magnet and the existence of a magnetic field caused by the rotation of electrons, a new theory speculates that there has also been a permanent magnetic field recently. In addition, the choice of gate charge and permanent magnets can be selected as potential energy which is also considered as possible which has been observed to exist but has not been well described. Equations have been derived electrons. In this respect, Islamic science and technology seems to have demonstrated the importance of exploring the mysterious quantum world.